SII as a predictor of mortality in patients with non-ST-segment elevation myocardial infarction and diabetes mellitus - Cuiyuan Huang; Jiajuan Yang; Wenqiang Li; Li Liu; Wei Wang; Haiyan Hu; Jing Zhang; Jian Yang (Practical Laboratory Medicine)
Background: Systemic immune inflammation index (SII) is an innovative marker reflecting immune and inflammatory responses. Objectives: To explore the predictive value of SII on the risk of death in patients with NSTEMI combined with T2DM. Methods: An analysis of 448 patients with NSTEMI and T2DM admitted to our institution between December 2017 and May 2022 was conducted in this retrospective study. SII values were used to divide patients into high and low SII groups and investigate their impact on mortality. Results: According to the analysis results, elevated SII levels are significantly linked to a poor prognosis in patients with NSTEMI and T2DM. Over an average follow-up period of 22.75 months, 106 (23.7 %) all-cause deaths were recorded. The optimal threshold for predicting death was found to be an SII value of 1384.596 × 109/L through ROC curve analysis. Kaplan-Meier analysis indicated that the survival rates were higher in the low SII group compared to the high SII group (P < 0.001). Elevated SII levels were independently linked to increased mortality in patients with NSTEMI and T2DM, according to univariate (HR:3.19, 95 % Cl: 2.18–4.68) and multivariate COX (HR: 2.72, 95 % Cl: 1.81–4.09) regression analyses. Conclusion: High SII values were strongly associated with mortality in patients with NSTEMI and T2DM. SII serves as a valuable prognostic tool, enhancing the management and prognosis of patients with concurrent NSTEMI and T2DM.